The Effectiveness of Health Education by Family Planning Development Group (BKR) with Media E Booklet and Module on Parents' Attitudes in Facing Adolescent Reproductive Health Problems - Arum Lusiana; Bambang Budi Raharjo; Widya Harry Cahyati; Evi Widowati (Universitas Negeri Semarang, 2023)
Background: Typical Traits Adolescents have a great sense of curiosity, love adventure and challenge and tend to dare to bear risks for their actions without being preceded by careful consideration. Adolescent problems related to reproductive health often stem from a lack of information and understanding and awareness toachieve reproductive health. Thus, the Indonesian government is working through several programs. One of the programs carried out through the family approach is BKR. Research Objective: To determine the effectivenessof health education by the Family Planning Development (BKR) group with E Booklet and Module on parents' attitudes in dealing with adolescent reproductive health problems Research Method: Themethod used in this study is quasi experiment with desain used in this study Pretest-Postest With Control Group Design. A sample of 40 respondents. Data collection in this study used a closed questionnaire about parental attitudes in dealing with adolescent reproductive health problems. Research Results: The results of the analysis of the Independent T-Test test obtained a p value of 0.000, which means that health education with E Booklet media by BKR members is more effective for parents' attitudes in dealing with adolescent reproductive health problems compared to the media Module by the BKR group Conclusions and Suggestions: Health education with E Booklet media by BKR is effective in dealing with parents' attitudes in dealing with adolescent reproductive health problems. In the community, especially parents of adolescents, to be able to better utilize the BKR services and programs that have been provided as a means of accessing information and discussion in addressing adolescent reproductive health problems.